Advances in Transdermal Drug Delivery Systems and Clinical Applications in Inflammatory Skin Diseases - Sizhuo Liu; Tinghan Deng; Hongbin Cheng; Jun Lu; Jingping Wu (Pharmaceutics, 2025)
Inflammatory skin diseases are highly prevalent conditions characterized by complex immune responses that result in skin tissue damage and pain, significantly impacting patients’ physical health. Traditional therapeutic approaches, including oral administration and injections, continue to exhibit inherent limitations. Consequently, there is growing interest in exploring alternative drug delivery systems that offer more effective, targeted, and patient-friendly therapeutic options. Transdermal administration emerges as a promising solution for managing inflammatory skin diseases, facilitating sustained drug release, and reducing the frequency of dosing. This review provides a comprehensive overview of the skin barrier and critically summarizes clinically adopted transdermal drug delivery systems (TDDSs), including sonophoresis, iontophoresis, chemical penetration enhancers, and electroporation. Particular emphasis is placed on emerging advances in microneedle- and nanocarrier-facilitated transdermal delivery strategies. Moreover, the article synthesizes recent fundamental evidence regarding the application of TDDSs in the treatment of atopic dermatitis, psoriasis, and acne. This review examines fundamental research evaluating various transdermal drug delivery systems for the treatment of major inflammatory skin diseases, with an emphasis on their mechanisms of action, advantages, challenges, and future directions. Transdermal drug delivery systems hold the potential to deliver more efficient and safer treatment and management strategies for patients afflicted with inflammatory skin diseases.